Bilateral functions for global motion modeling - Lin, W-YD; Cheng, M-M; Lu, J; Yang, H; Do, MN; Torr, P (Springer, 2014)
This paper proposes modeling motion in a bilateral domain that augments spatial information with the motion itself. We use the bilateral domain to reformulate a piecewise smooth constraint as continuous global modeling constraint. The resultant model can be robustly computed from highly noisy scattered feature points using a global minimization. We demonstrate how the model can reliably obtain large numbers of good quality correspondences over wide baselines, while keeping outliers to a minimum.